The righteousness of God a lexical examination of the covenant-faithfulness interpretation - Irons, Charles Lee 1968- (Tübingen Mohr Siebeck, 2015)
Advocates of the New Perspective on Paul appeal to the view that ""righteousness"" in biblical theology is a Verhältnisbegriff (relational concept). This is the view that ""righteousness"" does not mean conformity to a norm, nor is it an essentially legal concept; rather, ""righteousness"" denotes the fulfillment of the demands of a relationship, since the relationship itself is the norm. This relational interpretation of ""righteousness"" was first put forward by Hermann Cremer in 1899 and exercised a profound influence in biblical scholarship throughout the 20th century. It lies at the root
6. Letter of Aristeas
Description based upon print version of record
Keywords: Electronic books; Hochschulschrift